Analisis Kewenangan Diskresi Pejabat Daerah Perihal Pengalihan Anggaran - Octo Iskandar; Dzaky Perdana Dharmawan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
The government in carrying out its duties and functions must be based on existing legislation, but in accordance with the development and demands of the situation, not all laws and regulations are ready, because the creation of legislation requires a long time, on the other hand the government must do but the legislation does not exist, thus a legal vacuum will arise. In order to avoid the existence of a legal or regulatory vacuum, the State Administration Officer as the organizer of the government is given the authority to make a rule, or what is called Discretion or Freies Ermessen. Although State Administration Officers are given the authority to make a rule because of their needs, they must meet the following requirements: 1. There is freedom or freedom of the State Administration to act on its own initiative; 2. To resolve pressing issues that have no rules for that; 3. Must be accountable. Then corruption is Corruption comes from the corrupt word in English which means damaged, incomplete, error, cannot be used. Corruption has many meanings in its use as a word or sentence, and is not limited to criminal acts, but also means a thing, data, people, and human soul, which is in the understanding of the literature in Indonesian, English, and in computer languages, interpreted as something damaged and difficult to repair. Corruption in terms of human psychology, is interpreted as a person's soul that has been damaged or influenced by something so that the human soul or someone tends to do actions that are contrary to the philosophy of